THE DISTINCT POPULATION SEGMENT PROVISION OF THE ENDANGERED SPECIES ACT AND THE LACK THEREOF IN THE CALIFORNIA ENDANGERED SPECIES ACT (Utah Environmental Law Review; Vol 30 No 2 (2010), 2010)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In 1972, President Richard Nixon delivered a speech to the 93rd Congress in which he outlined a new and comprehensive environmental agenda. In his speech, the President called on Congress to adopt legislation that would provide the necessary management tools for the federal government to identify and protect endangered species. A year later Congress passed the federal Endangered Species Act of 1973 (FESA). FESA has specific provisions designed to foster smaller state-based endangered species acts; and in 1984, California adopted its version, the California Endangered Species Act (CESA). FESA differs from its California counterpart in a variety of ways. This Article highlights one of those differences- the authority to list and protect "distinct population segments" of species. The definition and application of the "distinct population segment" (DPS) power under FESA has been highly contentious. Recent court cases address issues such as the meaning of the DPS policy issued jointly by the United States Fish and Wildlife Service (FWS) and the National Marine Fisheries Service (NMFS) (collectively the Services); whether the DPS policy is entitled to Chevron deference; and the application of the DPS concept to salmon populations (which are termed evolutionarily significant units (ESUs)). These decisions focus on the meaning of FESA's DPS terminology, added to FESA in 1978. These debates have been absent under CESA for two related reasons. First, few populations smaller than an entire species or subspecies have been listed under CESA. Second, CESA expressly provides for "species or subspecies" listing but makes no reference to any smaller population. This Article analyzes whether CESA authorizes the listing of DPSs or ESUs. As a case-in-point, the Article uses the California Court of Appeal's recent decision in California Forestry Association v. Fish & Game Commission , which concerned a challenge to the California Fish and Game Commission's listing of two Coho salmon ESUs. The Article concludes that neither the text of CESA, nor the Act's legislative history, supports a DPS-ESU-listing power. The Article also offers some predictions as to the likely implications of the Court of Appeal's decision in California Forestry Association to uphold the Commission's DPS-listing power under CESA. Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}